KESALAHAN BERBAHASA DALAM PENULISAN BERITA PADA AKUN INSTAGRAM INDRAMAYU UPDATE PERIODE MARET HINGGA APRIL 2025 - Adilah, Supreti; Imas Juidah; Eli Herlina; Saroni (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study aims to analyze language errors in writing news on the Indramayu Update Instagram account for the period March to April 2025. Social media, especially Instagram, is one of the platforms used to disseminate information quickly and widely. However, sometimes language errors in writing can affect the understanding and credibility of the news. The method used in this study is qualitative descriptive analysis by identifying the types of language errors contained in the news text posted on the Instagram account. The language errors analyzed include spelling errors, punctuation, sentence structure, and incorrect use of words. Data were obtained by collecting news posts uploaded within a predetermined time period, then identifying and analyzing the language errors that appeared. The results of this study are expected to provide an overview of the quality of news writing on social media and the importance of good language understanding and skills in conveying information